Early Fetal Echocardiography: Ready for Prime Time? - Mirza, Fadi G.; Bauer, Samuel T.; Williams, Ismee A.; Simpson, Lynn L. (American Journal of Perinatology, 2012)
The objective of this study was to examine the performance of early fetal echocardiography as a screening tool for major cardiac defects in a high-risk population. Fetal echocardiograms performed at 12 to 16 weeks were reviewed. Cases that did not undergo a follow-up echocardiogram at 18 to 22 weeks were excluded. Results of the early and follow-up echocardiograms were compared. Over a 4-year period, 119 early fetal echocardiograms were recorded. Of those, 81 (68%) had follow-up fetal echocardiograms. Results of the early echocardiogram were normal in 77 of 81 (95.1%) cases. Of these, the follow-up was normal in 75 of these 77 cases; in the remaining 2, the follow-up raised suspicion for a ventricular septal defect (VSD) in one and persistent left superior vena cava in the other. On the other hand, the early echocardiogram was abnormal in 4 (4.9%) cases: (1) atrioventricular canal defect, with the follow-up demonstrating a VSD; (2) hypoplastic right ventricle and transposition of the great arteries, confirmed on follow-up; (3) VSD and coarctation of the aorta, confirmed on follow-up. In the fourth case, the early echocardiogram suspected a VSD and right-left disproportion, yet the follow-up was normal. In conclusion, early fetal echocardiography appears to be a reasonable screening tool for major cardiac defects.
Keywords: fetal echocardiography; fetal heart; congenital heart disease; prenatal diagnosis